Reformulating Product Liability for Autonomous Vehicles: A Comparative Analysis of Causation Theories in Indonesian and Kuwaiti Civil Law - Zein Samsia Ibrahim (Dalihan Na Tolu: Jurnal Hukum, Politik dan Komunikasi Indonesia, 2026)
The development of autonomous vehicles as a disruptive technological product presents serious challenges to civil law, particularly in determining manufacturer liability when accidents occur. The causation theory that underpins civil liability in Indonesia and Kuwait has not yet explicitly accommodated the complexity of artificial intelligence decisions, which are non-linear and multi-factorial. This research employs a normative legal method with a comparative law approach between the Indonesian Civil Code and the Kuwaiti Civil Code (Law No. 67 of 1980). The analysis reveals that Indonesian law, which alternately applies the conditio sine qua non theory and the proximate cause theory, fails to provide certainty and justice due to its binary approach. By contrast, Kuwaiti law adopts a gradation of causality through the distinction between al-sabab al-mubasyir (direct cause) and al-sabab al-mutasabib (indirect cause), and imposes strict liability for dangerous objects under Article 229. Based on this comparison, this study formulates a manufacturer liability reform through three pillars: tiered liability based on SAE automation levels, reversal of the burden of proving causality at high automation levels, and the establishment of mandatory insurance and a no-fault compensation fund. This reform requires amendments to the Indonesian Civil Code or the enactment of a special law on artificial intelligence and autonomous vehicles. In conclusion, Indonesia should adopt Kuwait's tiered approach to make manufacturer liability fairer, more adaptive, and legally certain in the era of technological disruption.